Assessment of nutritional status in children with acute respiratory failure: the prospective cohort observational study - O.V. Filyk (Danylo Halytsky Lviv National Medical University, 2020)
Pneumonia plays a significant role in the development of acute respiratory failure in children. The risk factors of pneumonia are malnutrition (weight to age relation according to scores), low birth weight ( < 2500 g), and other factors. Regardless of the  economic development of countries, the mortality rate in children with pneumonia admitted to intensive care units remains high (18-20%).